Shouldering the Burden of Evidence-Based Practice: The Experiences of Physiotherapists Partaking in a Community of Practice. (24th January 2016) - McCreesh, Karen; Larkin, Louise; Lewis, Jeremy
Abstract : The study aim was to elicit the motivators, barriers, and benefits of participation in a Community of Practice (CoP) for primary care physiotherapists. We used a qualitative approach using semistructured interviews. The participants were twelve physiotherapists partaking in a newly formed Shoulder CoP. A desire for peer support was the strongest motivator for joining, with improving clinical practice being less apparent. Barriers to participation included time and work pressures and poor research skills. The structure of the CoP, in terms of access to meetings and the provision of preparation work and deadlines for the journal clubs, was reported to be a facilitator. Multiple benefits ensued from participation. The role of teamwork was emphasised in relation to reducing isolation and achieving goals. The majority of participants reported positive clinical practice changes in terms of improved patient education, increased confidence, and availability of new resources. All participants reported some element of personal growth and development, in particular in their evidence-based practice skills. The results provide support for the use of CoPs as a means of continuing professional development for physiotherapists in the workplace, as significant benefits are gained in terms of evidence-based practice (EBP), patient care, and therapist personal development.